Answer:
(f + g)(3) = 22.
Explanation:
Given the following function operations:
(f + g)(x) if f(x) = 2x² and g(x) = 2x - 2, and that x = 3:
The function operation can also be expressed as follows:
(f + g)(x) = f(x) + g(x)
We could simply perform the required function operations separately, then add their results in the end. Substitute the value of x = 3 as an input into f(x) and g(x):
f(x) = 2x²
f(3) = 2(3)² = 2(9) = 18
Hence, f(3) = 18
g(x) = 2x - 2
g(3) = 2(3) - 2
g(3) = 6 - 2 = 4
g(3) = 4
(f + g)(x) = f(x) + g(x)
(f + g)(3) = f(3) + g(3)
(f + g)(3) = 18 + 4
(f + g)(3) = 22
Therefore, (f + g)(3) = 22.